2011
DOI: 10.2174/138945011795528859
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Targeted Plastoquinone Derivatives. Effect on Senescence and Acute Age-Related Pathologies

Abstract: Plastoquinone, a very effective electron carrier and antioxidant of chloroplasts, was conjugated with decyltriphenylphosphonium to obtain a cation easily penetrating through membranes. This cation, called SkQ1, is specifically targeted to mitochondria by electrophoresis in the electric field formed by the mitochondrial respiratory chain. The respiratory chain also regenerates reduced SkQ1H(2) from its oxidized form that appears as a result of the antioxidant activity of SkQ1H(2). SkQ1H(2) prevents oxidation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 93 publications
6
87
0
4
Order By: Relevance
“…This influence was detected 24 h after SkQR1 injection . Such relationships can decrease the GSK3β-mediated apoptosis involved in the neuronal Abeta toxic cascade in the brain (Lloret et al, 2011;Skulachev et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This influence was detected 24 h after SkQR1 injection . Such relationships can decrease the GSK3β-mediated apoptosis involved in the neuronal Abeta toxic cascade in the brain (Lloret et al, 2011;Skulachev et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria-targeted antioxidants include substances such as SkQ, MitoQ, MitoVitE, MitoPBN, MitoPeroxidase, glutathione choline esters, latrepirdine, and Szeto-Schiller (SS) peptides (Manczak et al, 2010;McManus et al, 2011;Skulachev et al, 2011;Calkins et al, 2012). One SkQ derivative, namely SkQ1, was the first mitochondria-targeted drug employed in medical practice (Yani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that substitution of ubiquinol to plastoquinol significantly improved the antioxidant properties of the compound in model membranes as well as in isolated mitochondria, living cells, and organisms (8). SkQ1was found to be a very efficient agent at preventing a variety of degenerative processes and prolonging the lifespan of fungi, invertebrates, and vertebrates in nanomolar doses (9)(10)(11)(12)(13)(14)(15)). We synthesized and tested several analogs of SkQ1, and in one of them (SkQR1) the phosphonium cation was substituted by the fluorescent cation rhodamine 19.…”
Section: Introductionmentioning
confidence: 99%
“…Пластохинонилдецилтрифенилфосфония бромид являет-ся активной субстанцией глазных капель Визомитин, первого в мире зарегистрированного лекарственного препарата с митохондриально-адресованным антиокси-дантом в качестве основного действующего вещества. Учитывая механизм терапевтического действия препара-та Визомитин, нами была рассмотрена возможность его использования у больных с НК [15][16][17][18].…”
unclassified